The Implementation of Mind Mapping Technique to Improve Student’s Reading Comprehension - Jamaluddin Nasution; Selviana Sari Dewi Sitepu; Rossa Anjelly Saragih; Jessica Sophie Hanna (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The problem of this research is students’ difficulties to comprehend the text because they had a weak vocabulary, lack interest in reading, and looked bored reading the text. By applying mind mapping techniques to narrative material, this study seeks to increase students' reading comprehension. In order to help students learn new vocabulary, access information from texts, and increase their memory for reading comprehension, this research employed class action research (CAR) with two cycles. The subjects of this research were students of the second grade at SMA S Panca Jaya Galang in the 2022/2023 academic year, totaling 25 students. This research uses data collection techniques in the observation sheet, tests, and documentation. This data was obtained from the pre-test and post-test results by applying the mind mapping. It has been found that teaching students how to use mind maps helps improve their reading comprehension. It can be seen from the data that in cycle I, 14 of 25 students only achieved a score of 75 or higher, the average student score was 66,4, with a total student score of 1660, and the proportion of pupils that succeed the KKM was approximately 56%. In cycle II, on the other hand, there were 21 of 25 students who achieved a score of 75 or higher, the average student score was 83,4, with a total student score of 2085, as well as the pass rate for students. The conclusion of this research is mind mapping techniques can improve students’ reading comprehension.